Teacher professional development during COVID-19 pandemic: Opportunities and challenges - Purwanti, Eko; Anggraini, Ririn; Agustina, Noor Qomaria (Universitas Ahmad Dahlan, 2023)
Teacher Professional Development (TPD) is any activities conducted by teachers to upgrade their teaching skills in order to maintain their professionalism. The activities of TPD have recently been greatly affected by the COVID-19 pandemic, resulting in the termination of almost all TPD activities. The study aimed at investigating TPD among English language secondary school teachers during the COVID-19 pandemic focusing on its opportunities and challenges. Using qualitative approach and descriptive qualitative research design, the study involved four English language teachers at two Secondary Schools in Yogyakarta as the participants. In-depth interviews with these four participants were conducted to achieve the objectives of this study. The findings of the study discovered that mastering the technology, improving the competency in designing online class, improving the competency in class management skill, and building peer collaboration among teachers were all the opportunities experienced by the teachers in conducting TPD activities during the COVID-19 pandemic. Moreover, teachers’ lack of digital competency, unstable internet network, limited number of TPD activities, and inadequate support system were the challenges experienced by these teachers in conducting TPD activities during the COVID-19 pandemic. These findings imply that despite the difficult times these English teachers faced during COVID-19 pandemic, they managed to improve their qualities as teachers by maximizing the opportunities of conducting TPD. Keywords: Professional, teacher competences, COVID-19 pandemi, Teacher Professional Development, opportunities, challenges